Análise do processo de despacho de ordens de serviço a campo: estudo de caso em uma empresa prestadora de serviços elétricos - Bezerra, Lucas Medeiros (Universidade Federal Rural do Semi-Árido, 2018)
Given the fierce competition, firms adopt different strategies to remain competitive in the market, among which stand out cost reduction and process improvement. In electric service companies, service order fulfillment is a complex task that is especially difficult when considering the high demand for services, the limited human and material resources available, and the need to observe quality and time established by the client and regulatory agencies, and failure to observe these deadlines implies fines to the service provider. Thus, this work aimed to contribute to the management of the process of dispatching service orders to the field, mapping it and identifying offenders, aiming to propose modifications in the process that provide positive impacts to productivity, respecting the limitations found in the system.
Monografia
Keywords: Serviços elétricos; Despacho; Processos; Electrical services; Dispatch; Processes; ENGENHARIAS::ENGENHARIA DE PRODUCAO